Information, the fuel of development - Njonga, Bernard (Technical Centre for Agricultural and Rural Cooperation, 1996)
Information in rural areas is essential to local development, whether it is acquired through study visits, meetings, informal networking, trading groups or publications. Information provides the basis for community decisions and is as necessary for...